Analysis of the hippo transducers TAZ and YAP in cervical cancer and its microenvironment. (2nd June 2016) - Buglioni, Simonetta; Vici, Patrizia; Sergi, Domenico; Pizzuti, Laura; Di Lauro, Luigi; Antoniani, Barbara; Sperati, Francesca; Terrenato, Irene; Carosi, Mariantonia; Gamucci, Teresa; Vincenzoni, Cristina; Mariani, Luciano; et al.
ABSTRACT: Hippo is a tumor-suppressor pathway that negatively regulates the oncoproteins TAZ and YAP. Moreover, Hippo affects the biology of a variety of non-neoplastic cells in the tumor microenvironment, even including immune cells. We herein assessed the predictive role of TAZ and YAP, assessed by immunohistochemistry, in 50 cervical cancer patients prevalently treated with neoadjuvant chemotherapy. Tumors were classified as positive or negative according to the percentage of tumor-expressing cells and cellular localization. TAZ/YAP were also evaluated in non-neoplastic cells, namely endothelial cells, non-lymphocytic stromal cells and tumor-infiltrating lymphocytes (TILs). TAZ expression in cancer cells (TAZ pos ) was associated with a reduced pathological complete response (pCR) rate ( p = 0.041). Conversely, the expression of TAZ and YAP in TILs (TAZ TIL+ and YAP TIL+ ) seemed to be associated with increased pCRs ( p = 0.083 and p = 0.018, respectively). When testing the predictive significance of the concomitant expression of TAZ in cancer cells and its absence in TILs (TAZ pos /TAZ TIL- ), patients with TAZ pos /TAZ TIL- showed lower pCR rate ( p = 0.001), as confirmed in multivariate analysis (TAZ pos /TAZ TIL- : OR 8.67, 95% CI: 2.31–32.52, p = 0.001). Sensitivity analysis carried out in the 41 patients treated with neoadjuvant chemotherapy yielded comparable results (TAZ pos /TAZ TIL- : OR 11.0, 95% CI: 2.42–49.91, p = 0.002). Internal validation carried out with two different procedures confirmed the robustness of this model. Overall, we found evidence on the association between TAZ expression in cervical cancer cells and reduced pCR rate. Conversely, the expression of the Hippo transducers in TILs may predict increased treatment efficacy, possibly mirroring the activation of a non-canonical Hippo/MST pathway necessary for T-cells activation and survival.